2011
DOI: 10.1007/s10530-011-9936-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal overlap of the alien invasive ctenophore Mnemiopsis leidyi and ichthyoplankton in the Bornholm Basin (Baltic Sea)

Abstract: In 2007 the alien invasive ctenophore Mnemiopsis leidyi A. Agassiz 1865 was recorded for the first time in the Bornholm Basin, an area which serves as important spawning ground for Baltic fish stocks. Since M. leidyi is capable of preying upon early life stages of fish and further might act as food competitor for fish larvae, it is of major concern to investigate the potential threat that this non-indigenous species poses to the pelagic ecosystem of the Baltic Sea. The present study investigates the temporal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…In the Black Sea, M. leidyi was collected only above the steep thermocline at 20 to 30 m in summer; importantly, the oxycline was much deeper (50−100 m; Mutlu 1999), suggesting that low oxygen did not determine the ctenophore depth distribution there. In the central Baltic Sea, peak densities of M. leidyi were at 62.5 to 72.5 m, below the pycnocline at ~55 m during the day (Schaber et al 2011); ctenophores may have avoided the cold waters (≤5°C) above the pycnocline, because DO (~2−6 ml l −1 ) and salinities above (~8) and below (~16) the pycnocline should not have restricted them. Thus, various factors may affect the vertical distribution of M. leidyi.…”
Section: Vertical Distributions Of Ctenophores Medusae and Copepodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Black Sea, M. leidyi was collected only above the steep thermocline at 20 to 30 m in summer; importantly, the oxycline was much deeper (50−100 m; Mutlu 1999), suggesting that low oxygen did not determine the ctenophore depth distribution there. In the central Baltic Sea, peak densities of M. leidyi were at 62.5 to 72.5 m, below the pycnocline at ~55 m during the day (Schaber et al 2011); ctenophores may have avoided the cold waters (≤5°C) above the pycnocline, because DO (~2−6 ml l −1 ) and salinities above (~8) and below (~16) the pycnocline should not have restricted them. Thus, various factors may affect the vertical distribution of M. leidyi.…”
Section: Vertical Distributions Of Ctenophores Medusae and Copepodsmentioning
confidence: 99%
“…Stratification of the water column and layering of the organisms have been studied extensively in the field with closing nets (e.g. Keister et al 2000, Schaber et al 2011 and at finer scales with acoustic, particlecounting, and camera systems (e.g. Cheriton et al 2007, Möller et al 2012, Bi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent warming has also been associated with an increase in invasive species in the Baltic region (Ojaveer et al 2011). An example of this is the relatively recent increase in Mnemiopsis leidyi, a ctenophore that will compete with ichthyoplankton for zooplankton prey resources and that can pose a direct predation threat for pelagic fish eggs and larvae (Haslob et al 2007;Schaber et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The vertical distribution of M. leidyi showed that it was mostly confined to water layers below the permanent halocline, and Schaber et al [32] suggested that food limitation plays a major role in the decline of M. leidyi in the central Baltic Sea during summer, and while they considered a self-sustaining population unlikely, they stated that M. leidyi is "most likely re-introduced" every year. Schaber et al [33] investigated the temporal and spatial overlap of M. leidyi and eggs and larvae of cod and sprat in order to assess the potential impact of the new invader on two of the most important Baltic fish stocks. The spatial overlap between M. leidyi and fish eggs and larvae was found to be low for most of the period observed, although situations with high overlaps were detected, for example for sprat larvae and cod eggs in spring, but on a general level it was concluded that M. leidyi "presently does not have a strong impact" [33].…”
Section: Occurrence In the Central Baltic Seamentioning
confidence: 99%
“…Schaber et al [33] investigated the temporal and spatial overlap of M. leidyi and eggs and larvae of cod and sprat in order to assess the potential impact of the new invader on two of the most important Baltic fish stocks. The spatial overlap between M. leidyi and fish eggs and larvae was found to be low for most of the period observed, although situations with high overlaps were detected, for example for sprat larvae and cod eggs in spring, but on a general level it was concluded that M. leidyi "presently does not have a strong impact" [33]. …”
Section: Occurrence In the Central Baltic Seamentioning
confidence: 99%